Safe ionic liquid-sulfolane/LiDFOB electrolytes for high voltage Li1.15(Ni0.36Mn0.64)0.85O2 lithium ion battery at elevated temperatures. (20th April 2018) - Dong, Liang; Liang, Fuxiao; Wang, Dong; Zhu, Caizhen; Liu, Jianhong; Gui, Dayong; Li, Cuihua
Abstract: In this study, 1-methyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)-imide (PP14 TFSI)-sulfolane/lithium difluoro(oxalato)borate (LiDFOB) based electrolytes with inherent thermal stability and low flammability are investigated as promising alternatives of conventional LiPF6 /carbonate electrolyte in high voltage Li/Li1.15 (Ni0.36 Mn0.64 )0.85 O2 cells at elevated temperatures. The safe and stable electrolyte candidates are selected by optimizing relative composition and represent high oxidative stability (higher than 5.2 V vs Li/Li + ) above 55 °C. The Li/Li1.15 (Ni0.36 Mn0.64 )0.85 O2 cells with E60 electrolyte achieved 172.5 and 238.8 mAh g −1 after 50 cycles between 2.0 and 4.6 V at 0.5C at 55 and 70 °C. Moreover, the Li/Li1.15 (Ni0.36 Mn0.64 )0.85 O2 cell with E60 electrolyte obtains a superior discharge capacity of 97.9 mAh g −1 at high rate of 3C at 70 °C. At extremely high temperature of 85 °C, the cell with E60 electrolyte delivers 218.7 mAh g −1 after 50 cycles at 1C. The excellent cycling performance in high voltage Li/Li1.15 (Ni0.36 Mn0.64 )0.85 O2 cells at elevated temperatures is attributed to the intrinsic oxidative stability and the compact and stable cathode-electrolyte interface (CEI) film derived from E60 electrolyte. We believe it a promising candidate that can be safely used for high voltage Li-rich cells at elevated temperature. Graphical abstract: